EFFECT OF OIL AND NON-OIL REVENUE OF THE FEDERAL GOVERNMENT ON THE ECONOMY OF NIGERIA (Journal of Contemporary Issues in Accounting, 2024)
The study investigated how the oil and the non-oil revenue of the Federal Government affects the Economy of Nigeria. The independent variables of this study are oil revenue, non-oil revenue, allocation from federation account, while dependent variable is real gross domestic product. The study adopted ex-post facto research design. The study covered the period 1981-2023, hence, maximizing the secondary source of data (time series data) collection that were collated from the CBN statistical bulletin and the National Bureau of Statistics (NBS) of various years. Relevant hypotheses were tested using the Ordinary Least Square analytical technique on the EVIEWS 10 statistical software. The results obtained revealed that generally, oil revenue had a negative and non-significant effect on real gross domestic product at (p> 0.05) of Nigeria during the period. On the other hand, it was discovered that the non-oil revenue and the allocation from federation account both had a positive and significant effect on real gross domestic product at (p
Keywords: Allocation from Federal Government; Non-Oil Revenue; Oil Revenue; Real Domestic Product.